Mineral-Oxide-Doped Aluminum Titanate Ceramics with Improved Thermomechanical Properties. (27th September 2012) - Papitha, R.; Buchi Suresh, M.; Das, Dibakar; Johnson, Roy
Abstract : Investigations were carried out, on the effect of addition of kaolinite (2Al2 O3 ·3SiO2 ·2H2 O) and talc (Mg3 Si4 O10 (OH)2 ) in terms of bulk density, XRD phases, microstructure, as well as thermal and mechanical properties of the aluminium titanate (AT) ceramics. AT ceramics with additives have shown enhanced sinterability at 1550°C, achieving close to 99% of TD (theoretical density) in comparison to 87% TD, exhibited with pure AT samples sintered at 1600°C, and found to be in agreement with the microstructural observations. XRD phase analysis of samples with maximum densities resulted in pure AT phase with a shift in unit cell parameters suggesting the formation of solid solutions. TG-DSC study indicated a clear shift in AT formation temperature with talc addition. Sintered specimens exhibited significant reduction in linear thermal expansion values by 63% (0.42 × 10 −6 /C, (30–1000°C)) with talc addition. Thermal hysteresis of talc-doped AT specimens showed a substantial increase in hysteresis area corresponding to enhanced microcrack densities which in turn was responsible to maintain the low expansion values. Microstructural evaluation revealed a sizable decrease in crack lengths and 200% increase in flexural strength with talc addition. Results are encouraging providing a stable formulation with substantially enhanced thermomechanical properties.